Drawing up the public national Rational Pharmacotherapy Action Plan as part of social and health services reform in Finland: a bottom-up approach involving stakeholders - Heidi Tahvanainen; Liisa-Maria; Katri Hämeen-Anttila; Ulla Närhi; Taina Mäntyranta; Anna-Riia Holmström; Marja Airaksinen (BMC, 2024)
Abstract Background Ensuring equal access to medicines and their appropriate and safe use at reasonable costs are core functions of health systems. Despite that, few descriptions of national medicines policies' development processes and implementation strategies have been published. This study aimed to describe the government program-based development of the Rational Pharmacotherapy Action Plan in Finland as a part of the undergoing major health and social service system reform, also covering the implementation of rational pharmacotherapy in the reformed system and processes. Methods The data of this qualitative study consisted of public reports and Steering Group meeting memos related to the development of the national Rational Pharmacotherapy Action Plan that the Ministry of Social Affairs and Health coordinated. Qualitative content analysis applying systems theory and the conceptual framework of integrated services as theoretical frameworks was used as an analysis method. Results The national Rational Pharmacotherapy Action Plan covering 2018-2022 was created in a bottom-up development process involving a wide range of stakeholders. Rational pharmacotherapy was redefined by adding equality as the fifth pillar to complement the previously defined pillars of being effective, safe, high-quality, and cost-effective. The Action Plan formed a normative framework for long-term development, with a vision and principles focusing on people-centeredness, better coordination and management of the medication use processes, the continuity of treatment paths and the flow of patient and medicines information through partnerships, and evidence-informed policies and practices. Conclusion Through intensive stakeholder participation, the bottom-up approach created a national vision and principles of rational pharmacotherapy along with strong commitment to implementing the goals and measures. The concern lies in ensuring the continuity of the Action Plan implementation and achieving a balanced long-term development aligned with the integrated and reformed national social and health services system. The development of the pharmaceutical system has several national and EU-level dependencies requiring political long-term commitment. While the Action Plan differs from the national medicines policy, it forms a good basis for long-term development covering important parts of medicine policy at the micro, meso, and macro levels of the service system.